Application of generative grammar for ukrainian sentences generation - Шестакевич, Тетяна Валеріївна; Висоцька, Вікторія Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2012)
This paper presents a generative grammar application in linguistic modeling